Acute Centro-facial Pigmentation – A sign of Viral Exanthem ?: Case Reports - Shilpakar, Rachana; Velugotla, Keerthi; Sachdev, M (Nepal Journal of Dermatology, Venereology & Leprology, 2017)
We report two cases of abrupt onset centro-facial pigmentation associated with acute viral fever and arthralgia. Review of literature yielded reports of similar pigmentation along with other dermatological manifestations like maculopapular rash, vesiculobullous lesions etc. In our cases centrofacial pigmentation confined to nose was the only presenting symptom and required treatment from patient’s perspective. Centro-facial melanosis may be considered as a sign of acute viral fever which could require specific treatment. The aim of our report is to widen the vision of clinicians in considering abrupt onset of centro-facial melanosis as a presenting symptom in an acute sero-negative viral fever with arthralgia.